Eukaryotic Signature Proteins - Han Jian; J. Collins Lesley (Journal of Proteomics and Genomics Research, 2012)
Eukaryotic Signature Proteins (ESPs) are proteins that delineate the eukaryotes from the archaea and bacteria. They have no recognisable homologues in any prokaryotic genome, but their homologues are present in all main branches of eukaryotes. ESPs are thus likely to have descended from ancient proteins that have existed since the first eukaryotic cell. The last dataset of ESPs was calculated more than a decade ago, thus with advances in technology and the rapid completion of many evolutionary important genomes, this dataset required recalculating. This study recalculated the Giardia lamblia ESP dataset and provides a procedure to calculate signature proteins beginning with any species. The G. lamblia ESP dataset contained a range of proteins including many associated with the membrane, cytoskeleton, nucleus and protein synthesis. ESP datasets have implications on current models of eukaryotic evolution, having high importance in phylogenetic analysis due to ESPs’ consistency and conservation in all eukaryotic species.
Keywords: Eukaryotic signature protein